2012
DOI: 10.3171/2012.7.focus12193
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidities, regional trends, and hospital factors on discharge dispositions and hospital costs after acoustic neuroma microsurgery: a United States nationwide inpatient data sample study (2005–2009)

Abstract: Object Hospitalization cost and patient outcome after acoustic neuroma surgery depend on several factors. There is a paucity of data regarding the relationship between demographic features such as age, sex, race, insurance status, and patient outcome. Apart from demographic factors, there are several hospital-related factors and regional issues that can affect outcomes and hospital costs. To the authors' knowledge, no study has investigated the issue of regional disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…18 On analysis we found that 81.33% of the patients with weekday admissions and 92.1% of those with elective admissions underwent surgery on the day of admission, compared with 17.52% of those with weekend admissions and 34.3% of those with nonelective admissions (p < 0.05). Interestingly, 0.9% of the pa- tients with nonelective admissions underwent surgery at another center 1 day prior to the admission at the index center, compared with 0.2% of the patients with elective admissions (p < 0.05), whereas none of those with weekend admissions underwent surgery prior to the admission at the index center.…”
Section: Hospital Factors and Outcomementioning
confidence: 95%
See 1 more Smart Citation
“…18 On analysis we found that 81.33% of the patients with weekday admissions and 92.1% of those with elective admissions underwent surgery on the day of admission, compared with 17.52% of those with weekend admissions and 34.3% of those with nonelective admissions (p < 0.05). Interestingly, 0.9% of the pa- tients with nonelective admissions underwent surgery at another center 1 day prior to the admission at the index center, compared with 0.2% of the patients with elective admissions (p < 0.05), whereas none of those with weekend admissions underwent surgery prior to the admission at the index center.…”
Section: Hospital Factors and Outcomementioning
confidence: 95%
“…As described in our study, discharge disposition to home was considered to be "routine" disposition as mentioned in the NIS, and discharges to all other places (Transfer to Short-Term Hospital, Skilled Nursing Facility, Intermediate Care Facility, Another Type of Facility, Home Health Care, Against Medical Advice, and Died) were categorized as "other than routine" (OTR) disposition. 18 Cost of the hospitalization was calculated using the variable "Total charges" (TOTCHG) in the NIS database. Percentiles of the cost were calculated and recoded as "high cost" (≥ 75th percentile, $74,284) and "low cost" (< 75th percentile) for the analysis.…”
Section: Outcome Factorsmentioning
confidence: 99%
“…2,32,49,51 In our study, the mean total hospital charge for initial in-hospital care was estimated to be $89,250 (in 2010 US dollars). Given that we investigated hospital charge rather than true payer cost, this cost is higher than a 2002-2003 estimate of mean payer cost for the 1st year of life of $50,000 ($59,250 in 2010 US dollars).…”
Section: Economic Burdenmentioning
confidence: 99%
“…An earlier study 20 has shown that hospital factors alone can affect clinical outcome. To understand the influence of hospital factors on patient outcome and complications, the following coded variables in the NIS database were studied: 1) region of hospital (in the NIS database, the US is divided into the following regions: Northeast, Midwest, South, and West), 2) ownership of hospital (government or private), 3) elective versus nonelective admission, 4) location of hospital (rural or urban), 5) bed size of hospital (small, medium, or large), 6) teaching status of hospital (teaching or nonteaching), 7) admission day 13 (MondayFriday vs Saturday-Sunday), and 8) transfer status/admis-sion status (direct admission or transfer-in from another facility).…”
Section: Methodsmentioning
confidence: 99%
“…20 OTR discharge dispositions included final outcomes like transfer to a short-term hospital facility, skilled nursing facility, intermediate care, or home health care; transfer against medical advice; and death. Discharge disposition to home without home health care was considered a routine discharge disposition.…”
Section: Methodsmentioning
confidence: 99%